Penerapan Analisis Sentimen Guna Meningkatkan Kualitas Pelayananan di Favehotel Solo Baru - Kusumastuti, Rajnaparamitha; Ardiansyahdiyan Anggoro Putro (Universitas Pelita Bangsa, 2025)
This analysis aims to provide convenience for hotel management in evaluating the quality and service at Favehotel Solo Baru so that the hotel gets good responses from the public regarding its quality. The application of sentiment analysis is used as a tool in evaluating quality and service in the hospitality industry. This analysis uses data on customer reviews at Favehotel Solo Baru and uses sentiment analysis techniques to analyze the review text. The use of this sentiment analysis is used for analysis with the Naive Bayes method. Sentiment analysis is also used to produce Heat Map, Word Cloud, and distribution visualizations on Orange Data Mining. The data used in this analysis consists of 270 reviews of visitors who have made reservations at the hotel. The data was taken using web scraping techniques on Google Maps. The scraping method used in collecting the data uses an extension from Google Chrome, namely Instant Data Scraper. The review scraping data was taken from 2017 to 2025. The results of this analysis show that sentiment towards visitor reviews is very good with 83.79% of people giving positive reviews and 74.07% of people giving a rating of 5.